The Gambia Integrated State-Owned Enterprises Framework (iSOEF) Assessment - World Bank (Washington, DC: World Bank, 2022)
This report applies the new World Bank integrated State-Owned Enterprises Framework (iSOEF) methodology to assess The Gambia´s SOE sector and its current reform trends. The report provides one of the first comprehensive applications of the World Bank’s new iSOEF methodology in Africa by providing first a landscape of SOEs in The Gambia, and then addressing key aspects for assessing SOEs, namely: “Effects on Markets”; “Fiscal Impact”; and “Corporate Governance and Accountability Mechanisms”. Leveraging the World Bank’s expertise across its Equitable Growth, Finance, and Institutions (EFI) Vice Presidency, this multidimensional assessment looks at the interrelationships of the challenges and opportunities faced by the Gambia´s SOEs to propose holistic and sequenced recommendations to strengthen their governance and performance. The primary audience of the iSOEF is the Government of The Gambia, in particular the Ministry of Finance and Economic Affairs (MOFEA) and other relevant stakeholders.